Brain laterality, depression and anxiety disorders: New findings for emotional and verbal dichotic listening in individuals at risk for depression. Issue 4 (1st November 2016) - Bruder, Gerard E.; Alvarenga, Jorge; Abraham, Karen; Skipper, Jamie; Warner, Virginia; Voyer, Daniel; Peterson, Bradley S.; Weissman, Myrna M.
ABSTRACT: Studies using dichotic listening tests and electroencephalographic (EEG) measures of hemispheric asymmetry have reported evidence of abnormal brain laterality in patients having depressive disorders. We present new findings from a multigenerational study of risk for depression, in which perceptual asymmetry was measured in dichotic listening tests of emotional and verbal processing. Biological offspring and grandchildren of probands with a major depressive disorder (MDD) who were at high risk and those of nondepressed controls who were at low risk were tested on dichotic emotional recognition and consonant–vowel syllable tests. In the emotion test, individuals with a lifetime diagnosis of MDD had a smaller right hemisphere advantage than those without a MDD, but there was no difference between high- and low-risk groups or between those with or without an anxiety disorder. In the syllable test, a smaller left hemisphere advantage was found in individuals with an anxiety disorder compared to those without an anxiety disorder, but there was no difference between high- and low-risk groups or between those with or without a MDD. This double dissociation indicates that lifetime diagnosis of MDD and anxiety disorders have a differential impact on lateralized hemispheric processing of emotional and verbal information.